Jamur Kontaminan Pada Nasi Berdasarkan Cara Penyimpanan: Contaminant Fungus In Rice Based On Storage Method - Agustina, Shella; Azahra, Sresta; Kusumawati, Nursalinda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Rice is a staple food for the people of Indonesia as a source carbohydrate. Improper rice storage can lead to contamination microorganisms. One of these microorganisms is fungus. Contaminant mold is an example of a type of fungus that can grow on foodstuffs such as rice. This study aims to determine the description of fungal contaminants in rice with various kinds of storage, namely rice cooker on, rice cooker off, and serving lid with storage time of 8 hours, 16 hours, and respectively 24 hours. This type of research is a descriptive observational approach cross sectional. The sample uses 3 brands of rice taken from the market Segiri Kota Samarinda with purposive sampling technique. Rice is processed then stored in various places and storage times. After that identification of contaminants macroscopically and microscopically. Data analyzed using univariate analysis. The results of the research show that there is 3 species of contaminating fungi namely Aspergillus sp, Muchor sp, and Penicillium sp. Based on the sample storage with rice cooker on, rice cooker off, and serving cap respectively indicate the percentage growth of the species the same fungus, namely 33.3%.